Pengaruh Wet Cupping terhadap Kadar Hemoglobin Darah Vena Orang Sehat - Pranata, Lilik (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Wet cupping known as blood letting in western countries has long been done since the Hippocrates. Hijamah or cupping (other languages, coke, cupping, cupping) is a therapy that aims to cleanse the body of blood which contains toxic with thin slices or small punctures on the surface of the skin, Wet Cupping is developed as an alternative and complementary treatment, the purpose of the study is to determine the effect of wet cupping against healthy blood vein hemoglobin levels. This research method with experimental clinical test with pre and post intervention design without control group. The implementation of wet cupping is carried out at Puskesmas Palembang Campus and blood collection and blood tests at the Health Laboratory Center (BBLK) of South Sumatra Province. The sample of this study was 30 respondents with an age range of 18-22 years, the parameters seen were the value of hemoglobin levels, the treatment was carried out after 8 hours of intervention. To control confounding factors in this study, respondents before getting treatment were not allowed to exercise and heavy activities and still consume daily food without additional food. The results of the study showed a significant increase in hemoglobin levels, 8 hours after wet cupping was performed on healthy venous blood, the mean hemoglobin level was 15.08 Â± 0.63, increasing to 15.45 Â± 0.76. The conclusion that wet cupping affects healthy people's venous blood hemoglobin levels, it is hoped that wet cupping can be used in alternative and complementary therapies.